Brazilian technology policies in education: History and lessons learned - José Armando Valente; Maria Elizabeth Bianconcini de Almeida (Arizona State University, 2020)
Brazilian initiatives aimed at the insertion of information and communication technologies (ICT) in K-12 education took their first steps in the 1970s, when several countries focused their efforts on the use of ICT in the educational context. Since the early 1980s, a number of public policies have been created that have given rise to various projects and programs developed at the national level. The objective of the article is to analyze these policies using the Four in Balance model resignified for the Brazilian reality. The methodology is based on a study of documents. The EDUCOM Project, the Immediate Action Program in Informatics in Education, and the national programs, PRONINFE and ProInfo, were analyzed. The results show that these projects and programs did not always balance the axes of vision, teacher and manager training, digital educational resources and infrastructure, and cross-curricular evaluation and research. From this analysis it was possible to highlight some lessons and suggestions for future public policies related to the implementation of technologies in education.